Affinity Chromatography‐Based Assays for the Screening of Potential Ligands Selective for G‐Quadruplex Structures. Issue 5 (24th May 2022) - Platella, Chiara; Napolitano, Ettore; Riccardi, Claudia; Musumeci, Domenica; Montesarchio, Daniela
Abstract: DNA G‐quadruplexes (G4s) are key structures for the development of targeted anticancer therapies. In this context, ligands selectively interacting with G4s can represent valuable anticancer drugs. Aiming at speeding up the identification of G4‐targeting synthetic or natural compounds, we developed an affinity chromatography‐based assay, named G‐quadruplex on Oligo Affinity Support (G4‐OAS), by synthesizing G4‐forming sequences on commercially available polystyrene OAS. Then, due to unspecific binding of several hydrophobic ligands on nude OAS, we moved to Controlled Pore Glass (CPG). We thus conceived an ad hoc functionalized, universal support on which both the on‐support elongation and deprotection of the G4‐forming oligonucleotides can be performed, along with the successive affinity chromatography‐based assay, renamed as G‐quadruplex on Controlled Pore Glass (G4‐CPG) assay. Here we describe these assays and their applications to the screening of several libraries of chemically different putative G4 ligands. Finally, ongoing studies and outlook of our G4‐CPG assay are reported. Abstract : Ligands selectively targeting DNA G‐quadruplexes (G4s) represent valuable targeted anticancer drugs. Aiming at speeding the identification of G4‐targeting ligands, the affinity chromatography‐based assay named G‐quadruplex on Oligo Affinity Support (G4‐OAS) was developed, by synthesizing G4‐forming sequences on commercial polystyrene OAS. Then, due to unspecific binding of hydrophobic ligands on nude OAS, a universal support based on Controlled Pore Glass (CPG) was conceived for both G4‐forming oligonucleotides synthesis and affinity chromatography‐based assay, renamed as G‐quadruplex on Controlled Pore Glass (G4‐CPG) assay.